The Bahamas : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The Bahamian economy began a tepid recovery in 2010, following a sharp recession in 2008 and 2009 in the wake of the global financial crisis. Real GDP grew by about 1 percent. The rebound was driven by the trade, hospitality, transport, and government services sectors. Executive Directors welcomed the gradual recovery of the Bahamian economy. They also called for steadfast implementation of reforms to place public debt on a sustainable path, build fiscal buffers, and enhance medium-term growth prospects.